Analisa Posisi Keuangan Perusahaan Dalam Hubungannya Dengan Profitabilitas Perusahaan Pada UD. â€œDâ€ Di Kota Ambon - Sherly Rutumalessy (Jurnal Administrasi Terapan, 2023)
This research aims to determine the company's financial position in relation to the company's profitability, where the data used in this research are the company's financial reports consisting of a balance sheet and profit and loss report for 3 years, namely from 2020 to 2022.The research results show that the gross profit margin in 2020 was 0.14; in 2021 it will be 0.15 and in 2022 it will be 0.14 from every Rp. 1.00 in sales. The operating income ratio in 2020 is 0.96%; in 2021 it will be 0.65% and in 2022 it will be 0.75%. Meanwhile, the net profit margin (net profit) of the company's ability to generate profits fluctuates, namely in 2020 it was 0.86%; in 2021 it will decrease to 0.59% and in 2022 it will increase by 0.68%. And to find out the company's ability to generate profits from invested capital (earning power), in 2020 it was 4.03%; down by 2.73% in 2021 and in 2022 up by 3.19%. The liquidity ratio consisting of the current ratio and quick ratio for 3 years (2020-2022) experienced fluctuations, where the current ratio in 2020 was 1.69; decreased in 2021 by 1.66 and increased by 1.74 in 2022. Meanwhile, the quick ratio in 2020 was 0.56, rose to 0.58 in 2021 and increased in 2022 by 0.63. The leverage ratio consists of the total debt to equity ratio, where for 3 years the company's ability to use capital has fluctuated, namely in 2020 it was 2.69; in 2021 it will be 1.45 and in 2022 it will increase by 2.09. The long term debt to equity ratio also experienced fluctuations, where in 2020 it was 0.74, down by 0.12 in 2021 and in 2022 it rose by 0.54. As the total debt to equity ratio experiences fluctuations, for 2020 it is 0.65; in 2021 it will be 0.55 and in 2022 it will be 0.63The activity ratio is intended to measure the company's ability to use funds, which in this ratio consists of total assets turnover, where assets rotating in a period, namely the period 2020 to 2022, have increased, also for inventory turnover during 2020 to 2022 has experienced fluctuations, namely in 2020 11.77 times; in 2021 it will be 12.76 times and in 2022 it will be 11.70 times. And for working capital turnover, in 2020 the turnover was 1.95 times, in 2021 it was 2.05 times and in 2022 the turnover was 1.90 times.Keywords: Financial position, Profitability